Development of a model for the management of the Urama wetland, Venezuela (2021)
The concept of management has recently been integrated into ecology as a planned, dynamic and continuous process. The global ecological commitment establishes environmental protection goals by implementing protected areas (PAs). Management planning consists of defining the objectives with respect to the ecological characteristics, processes and values of the ecosystem. The objective of the research is to develop a model for the management of the Urama wetland (HU), Venezuela, based on the analysis of the wetland management policies and strategies of 14 Latin American countries plus Spain. The model applies the assessment of the components of the Ramsar Convention: Policy, ecological character, assessment, objectives, and action plan. As a result, a Wetland Management Model Indicator (WMMI) has been obtained, whose integral quantitative value is 0.67, the maximum being equal to 1. For the qualitative valuation of the WMMI, 13.3% reaches the category “very high”, 33.33% “high”, 20% “medium” and 33.33% “low”. With this result, a model for HU management is developed, integrating 5 components, 28 variables and 56 attributes for a diagnosis and evaluation process, considering the impact variables for the decision making of the Action Plan.